Enhancing EFL students’ reading comprehension through Instagram: A quasi-experimental study - Sudiran, Sudiran; Taufiq, Wahyu; Adi, A.B. Prabowo Kusumo (JEES (Journal of English Educators Society), 2025)
The rapid development of digital technology has reshaped students’ learning preferences, particularly in accessing reading materials. Despite the abundance of digital resources, many students still struggle to develop sufficient English reading skills, indicating a need for innovative media that align with their learning habits. While several studies have investigated social media as a supplementary learning tool, limited research has specifically examined the systematic use of Instagram in enhancing students’ reading comprehension. Therefore, this study aimed to examine the implementation of Instagram as a learning medium to improve students’ reading skills and to measure its effectiveness in classroom practice. A quasi-experimental design was employed with 28 university students, who were taught with Instagram-based reading materials. Reading materials were selected from authentic Instagram posts and delivered during eight instructional sessions over eight weeks. Data were collected through validated and reliable reading comprehension tests administered as a pretest and post-test. In addition, a student reading test was used to capture learners’ skills in Instagram-based reading activities. The findings revealed that students’ post-test scores significantly outperformed their pre-test scores, with a notable increase in their mean post-test scores (M = 69.00) compared to the pretest scores (M = 59.60). Independent samples T-test analysis confirmed a statistically significant difference (p < 0.05), indicating that Instagram effectively supports reading comprehension improvement. Moreover, students reported higher motivation and engagement when learning through Instagram. These results suggest that Instagram can serve as an innovative and authentic medium to enhance reading skills in EFL contexts.